EFFECTIVENESS OF TRANSCRANIAL DURAL REPAIR FOR EARLY POST-TRAUMATIC CEREBROSPINAL FLUID LEAKS - Rahman, Zia Ur; Mukhtar Khan, Muhammad (Journal of Postgraduate Medical Institute, 2018)
Objective: To determine the effectiveness of transcranial dural repair in the management of early traumatic cerebrospinal fluid (CSF) rhinorrhea. Methodology: This study was conducted at Department of Neurosurgery, Ha- yatabad Medical Complex, Peshawar, from March 2015 to February 2017. Cases of traumatic CSF rhinorrhea of less than 7 days' duration, from both genders without age discrimination were included. Patients with chronic, spontaneous and iatrogenic CSF leaks were excluded. CSF rhinorrhea was diagnosed on clin- ical as well as radiological studies. Results: Total 60 patients were studied. Age range was 7 to 57 years with mean age of 29 ±1.2 years. There were 46 (76.6%) males and 14 (23.3%) were fe- males. The causes of head trauma were road traffic accident in 36 (60%), fall from height in 14 (23.3%) and miscellaneous were noted in 10 (16.67%). Overall, postoperative complications were observed in a total of 13 (21.7%) patients. The success rate as denoted by closure of the CSF leak was 90%. Complications of surgery included recurrent CSF leak in 6 (10%) patients, 4 (6.67%) patients had meningitis, 10 (16.67%) patients developed pneumocephalus while 06 (10%) patients were complaining of loss of smell after surgery. Conclusion: Transcranial dural repair is the safe and effective way to treat post-traumatic CSF rhinorrhea and prevent its complications.